THE INFLUENCE OF PARENTING STYLES AND ACHIEVEMENT MOTIVATION ACHIEVEMENT ON STUDENTS GRADE X DEPARTMENT LEARNING AT ONE OF SMKN IN JAKARTA - Permata, Resta Dila; Zain, Nuryetty; Munawaroh (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This study aims to determine whether there is an influence of parenting styles and achievement motivation on students grade X department learning achievement at one of public vocational schools in Jakarta. This research was conducted for 6 months from January to Juny 2018. The research method is survey method with correlational approach. The population is students grade X which amounts to 214 students. The sample used 130 students and using the proportional random sampling technique. Variable Y (Learning Achievement) data is secondary, while variable X1 (Parenting Styles) and X2 (Achievement Motivation) data is primary using Likert scale. The data is tested for validity and reliability, and then analysis with multiple regression technique and classical assumption test. The data were analyzed using SPSS 22.0 version. The results showed there is a significant influence between Parenting Styles and Achievement motivation on students learning achievement with a regression equation Ŷ = 11,065 + 0,211X1 + 0,735X2. The results of F test in ANOVA table produces Fcount 106,976 > Ftable 3,07, this means parenting styles and achievement motivation simultaneously positively influence the learning achievement. The t test produces tcount X1 2,117 > ttable 1,656, because tcount > ttable that means there is a positive influence between parenting styles and learning achievement. And then tcount X2 8,863 > ttable 1,656, because tcount > ttable that means there is a positive influence between achievement motivation and learning achievement. And then from the coefficient determination was obtained 0,628, which means there is an influence of independent variable on dependent variable in the amount of 62,8% and the remaining of 37,2% was influenced by the other variable who not be examined.